(untitled) (Bangladesh Journal of Medicine, 2015)
Background: Thalassemia is considered the most common genetic disorder worldwide and about 7% of world populations are carriers. A vast majority of such cases have iron deficiency. Objective: This study was undertaken to find out the pattern of iron status in thalassemia traits and thus to determine co-existing iron deficiency in them. Method: This cross sectional study was carried out in the Department of Hematology, BSMMU, Dhaka from January 2007 to December 2007. Adult anemic patients of hypochromic microcytic blood film attending outpatient department were screened for thalassemia on the basis of clinical history, physical findings and hemoglobin electrophoresis. A total of 50 anemic patients with carrier state of thalassemia was detected and selected for evaluation of iron profile. Results: Patients having iron deficiency detected by serum iron profile were compared with those without iron deficiency. The mean age in years of study subjects were 30.38 ± 9.79 years. Among the study population, 50% were male and 50% were female. Highest frequency of co-existent iron deficiency was found among the age of 21-30 years. Prevalence of iron deficiency was 30.2% among b-thalassemia trait. A statistically significant mean difference of Hb, MCV, MCH, MCHC, serum iron, TIBC, S. Ferritin, transferring saturation was found indicating study subjects without iron deficiency had higher level than with iron deficiency (p<0.05). Conclusion: Clinical iron deficiency may occur in thalassemia trait/carriers of inherited hemoglobin disorders. The combined state should always be suspected and iron supplements are often needed to improve the status of anemia. Bangladesh J Medicine Jan 2014; 25 (1) : 13-16